2007
DOI: 10.1308/003588407x155473
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current Practices in Breast Conservation Surgery in the UK

Abstract: The results show a large variation in practice with many surgeons not treating patients in accordance with current guidelines and evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…The aim of breast conservative surgery is long-term disease control through excision of all of invasive and in situ cancer. Breast conservative surgery is as effective as mastectomy in terms of overall survival, ensures a good cosmetic result, and has many advantages in terms of psychological effects and quality of life (6,7). Surgical criteria for patient selection for breast conservative surgery include the following parameters: tumor extent, presence of unifocal tumors relative to the size of the breast ("tumor size to breast volume" ratio), tumor location, and patient preference (6,8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of breast conservative surgery is long-term disease control through excision of all of invasive and in situ cancer. Breast conservative surgery is as effective as mastectomy in terms of overall survival, ensures a good cosmetic result, and has many advantages in terms of psychological effects and quality of life (6,7). Surgical criteria for patient selection for breast conservative surgery include the following parameters: tumor extent, presence of unifocal tumors relative to the size of the breast ("tumor size to breast volume" ratio), tumor location, and patient preference (6,8).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore the data concerning the type of surgery do not always follow the radiological findings as the poor shift from mastectomy to breast conservative surgery after NACT is related to the surgeons' attitude for aggressive approach despite the response to NACT (6,8,37). Another limitation of the DCE-MRI examination is its relatively low specificity.…”
Section: Discussionmentioning
confidence: 99%
“…This difference between groups was found to be statistically significant and the same significant trend favoring not to reexcise was seen amongst surgeons participating in weekly tumor boards and those trained in surgical oncology. Another questionnaire study involving 200 breast surgeons in the United Kingdom showed less variation in surgeon practices with 91% of respondents favoring no further surgery if there was ADH at the margin of excision, but both invasive and in situ disease were 10 mm clear of the margin [20]. …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, despite the high volume of studies investigating the question of adequate margin width, there is a paucity of studies that address the pathological characteristics of the cells within the margin. Not surprisingly, in the setting of no evidence-based guidelines, neither pathologists nor surgeons know what to do with the diagnosis of ADH involving a margin of a BCS specimen performed for early-stage breast cancer [1820]. The purpose of this paper is to address the significance of a diagnosis of ADH at the margin and evaluate if there is evidence to guide the surgical decision for reexcision.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the criteria for an adequate negative margin had relatively arbitrary thresholds ranging from “no tumor at inked margin” to 10mm or more [12,17]. Although absence of tumor at the inked margin is the current recommendation from national clinical consensus guidelines [15,16], there has been considerable variation in practice patterns among surgeons regarding the decision to re-excise or perform a mastectomy based on margin distance [2,18,19]. …”
Section: Introductionmentioning
confidence: 99%